Lifestyle and socio-economic disparities in the prevalence of diabetes among the elderly population (aged 60+) in India: a decomposition analysis using longitudinal aging study in India data - Panda, Paramjot (International Journal Of Community Medicine And Public Health, 2023)
Background: This study aimed to determine the prevalence of self-reported diabetes by sex and investigate the socio-economic, demographic, and lifestyle risk factors associated with diabetes. Additionally, it aimed to understand the coexistence of diabetes with other morbid conditions. Methods: The study design used in this research is a cross-sectional study design. This study utilized data from the longitudinal aging study in India (LASI), a nationally representative survey of older adults. The sample included 15,098 males and 16,366 females aged 60 years and above. Results: The prevalence of diabetes in India varies by state, zone, and rural/urban areas. Kerala has the highest prevalence among both men (33%) and women (28.5%). Urban areas have a higher prevalence (20%) compared to rural areas (8.5%). Hypertension and cancer are strongly associated with diabetes. Other morbid conditions like heart disease, high cholesterol, and vision problems also show significant links with diabetes. Conclusions: Diabetes in India is a significant health concern, with variations across regions and associations with comorbidities like hypertension, cancer, heart disease, high cholesterol, and vision problems. To address this, comprehensive preventive measures and health promotion campaigns are needed, targeting high-risk groups and improving healthcare access. Early detection, effective management, and promoting healthy lifestyles are crucial for diabetes prevention and control in India.